2004
DOI: 10.1124/jpet.104.075994
|View full text |Cite
|
Sign up to set email alerts
|

Positional Isomerism Markedly Affects the Growth Inhibition of Colon Cancer Cells by Nitric Oxide-Donating Aspirin in Vitro and in Vivo

Abstract: NO-donating aspirin (NO-ASA), a novel pharmacological agent currently undergoing clinical testing, consists of ASA to which a nitrate group is covalently linked via a spacer molecule. We synthesized the three positional isomers of NO-ASA with respect to the -CH 2 ONO 2 group (ortho, meta, and para) and examined whether this isomerism affects the biological activity of NO-ASA on HT-29 human colon cancer cells. The ortho-and para-isomers showed similar IC 50 values (1-5 M) for cell growth inhibition over 72 h, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 15 publications
4
72
0
Order By: Relevance
“…To a first approximation, NO-NSAIDs have a strong cell growth inhibitory effect, which is the end result of three individual effects: inhibition of cell proliferation, induction of apoptosis and deceleration of cell cycle phase transitions [19,[29][30][31]. The most detailed study on the induction of apoptosis was conducted by Gao et al [32], whose work on NO-ASA highlighted three important aspects of this effect: a) the first recognizable effect was the induction of oxidative stress; b) this was followed by activation of the intrinsic apoptosis pathway; and c) inhibition of Wnt signaling was a major component of the proapoptotic effect of NO-ASA.…”
Section: Evidence For the Anticancer Effect Of No-nsaidsmentioning
confidence: 99%
“…To a first approximation, NO-NSAIDs have a strong cell growth inhibitory effect, which is the end result of three individual effects: inhibition of cell proliferation, induction of apoptosis and deceleration of cell cycle phase transitions [19,[29][30][31]. The most detailed study on the induction of apoptosis was conducted by Gao et al [32], whose work on NO-ASA highlighted three important aspects of this effect: a) the first recognizable effect was the induction of oxidative stress; b) this was followed by activation of the intrinsic apoptosis pathway; and c) inhibition of Wnt signaling was a major component of the proapoptotic effect of NO-ASA.…”
Section: Evidence For the Anticancer Effect Of No-nsaidsmentioning
confidence: 99%
“…Interestingly, the pharmacologic profile of NO-ASA seems to be dependent on the positional isomerism, with different isomers showing varying efficacies in different disease backgrounds (20). The para-isomer, for example, was shown to be a very potent inducer of apoptosis in colon cancer cell lines and in an intestinal cancer mouse model (21). The same group demonstrated a disruption of the b-catenin/Tcf/ Lef-1 complex as a potential mechanism of NO-ASA action in colon cancer (13,22), a tumor where 100% of cases show an aberrant activation of Wnt/b-catenin/Tcf/Lef-1 signaling due to an APC or a CTNNB1 (b-catenin) mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the mechanism of their enhanced potency has not been fully clarified. Converging lines of evidence underscore the vital role of the NO-releasing moiety, and a recent report showed an excellent correlation between the amount of NO released by NO-NSAIDs and their ability to inhibit the growth of cultured colon cancer cells (6). In vitro data have shown that NO-NSAIDs have been invariably more potent than their parent compounds, although their enhanced potency ranged between 10-to >1,000-fold (7).…”
Section: Introductionmentioning
confidence: 99%